PROFIL PENGGUNAAN OBAT PADA PASIEN DEPRESI RAWAT JALAN DI APOTEK “X” DENPASAR PERIODE JANUARI-APRIL 2022 - Putu Ika Indah Indraswari; Ni Luh Sudi Astini; Ella Yunita (Journal Pharmactive, 2022)
Depression is a mood disorder characterized by deep feelings of sadness and indifference The symptoms of depression in adolescents are often characterized by feelings of irritability, distress, fear, lacklusterness, sadness, conflicts with friends, and conflicts with family. The highest incidence of depression was in the Southeast Asian region of 86.94 (27%) out of 322 billion individuals. Indonesia itself is in fifth place with a depression incidence rate of (3.7%). This study aims to determine the profile of drug use in outpatient depression patients at Karuna Pharmacy for the period January-April 2022. This research is a descriptive research that uses a cross-sectional research design with a retrospective approach and is processed qualitatively. The results of a study of 110 patients who entered the inclusion criteria, namely the use of antidepressants, namely selective serotonin reuptake inhibitors (SSRI) class drugs with a combination of psychotropic group drugs with a total of 53 (48.18%) people.